2019
DOI: 10.29333/ojcmt/5863
|View full text |Cite
|
Sign up to set email alerts
|

British or American English: Emerging Trends in Pakistani English Newspapers

Abstract: This paper analyses the features of American English found in Pakistani English newspapers and accounts for those features quantitatively with reference to British English. Pakistani journalistic English has the tendency to become more Americanized in the recent era. There is a shift from British English to American English in Pakistani newspapers and this brief study aims to show the growing influence of American English on Pakistani English. American English is considered the most influential and powerful va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Several studies have been conducted to explore English varieties used both American English and British English in different context (Ali et al, 2020;Anwar & Qureshi, 2019;Audriyan & Putri, 2021;Baratta & Halenko, 2022;Boonsuk et al, 2021;Carrie & McKenzie, 2018;Chung & Miki Bong, 2019;Chvala, 2020;DaCosta & Arias, 2021;Dirgeyasa, 2015;Eriksson, 2019;Fares, 2019;Gunawan & Aminah, 2020;Hadjoudji, 2019;Han, 2019;Hermini, 2019;Kiavar & Yaghoubi-Notash, 2019;Leemann et al, 2018;Passakornkarn & Vibulphol, 2020;Raihan, 2021;Rezaei et al, 2019;Serrarens, 2017;Toscu, 2019;Yaman, 2015). In Indonesian context, there are several studies have conducted regarding students' awareness of the differences between the American and British English, a study from Gunawan & Aminah (2020) they found that although the students have demonstrated a greater level of mastery of American and British English, they still have trouble telling the two forms apart and frequently utilize both varieties.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to explore English varieties used both American English and British English in different context (Ali et al, 2020;Anwar & Qureshi, 2019;Audriyan & Putri, 2021;Baratta & Halenko, 2022;Boonsuk et al, 2021;Carrie & McKenzie, 2018;Chung & Miki Bong, 2019;Chvala, 2020;DaCosta & Arias, 2021;Dirgeyasa, 2015;Eriksson, 2019;Fares, 2019;Gunawan & Aminah, 2020;Hadjoudji, 2019;Han, 2019;Hermini, 2019;Kiavar & Yaghoubi-Notash, 2019;Leemann et al, 2018;Passakornkarn & Vibulphol, 2020;Raihan, 2021;Rezaei et al, 2019;Serrarens, 2017;Toscu, 2019;Yaman, 2015). In Indonesian context, there are several studies have conducted regarding students' awareness of the differences between the American and British English, a study from Gunawan & Aminah (2020) they found that although the students have demonstrated a greater level of mastery of American and British English, they still have trouble telling the two forms apart and frequently utilize both varieties.…”
Section: Introductionmentioning
confidence: 99%